The Effect of Self-Control on Academic Procrastination - Parsaoran, Imron; Sugiyo, Sugiyo; Mugiarso, Heru (Jurnal Bimbingan Konseling, 2023)
Various academic tasks at vocational high school or Vocational High School and their deadlines urge the issue of academic procrastination. Of this issue, the present study aimed at discovering the effect of self-control on the academic procrastination of Vocational High School students. It used a quantitative approach and involved 379 students (227 male and 152 female students) with the age range of 14-17 years. Their data were collected using the scales of self-control and academic procrastination. Findings indicated a negative relationship between self-control and academic procrastination. It infers that students with high self-control seem to be able to manage themselves from disruptive behavior that is not in line with their goals.